2017
DOI: 10.1071/wr16108
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of road mortality of medium–large mammals in Mato Grosso do Sul, Brazil

Abstract: Context Brazil has one of the richest biodiversity and one of the most extensive road networks in the world. Several negative impacts emerge from this interaction, including wildlife–vehicle collisions (WVC), which may represent a significant source of non-natural mortality in several species. The understanding of the main drivers of WVC is, therefore, crucial to improve the safe coexistence between human needs (transportation of goods and people) and animal populations. Aims We aimed to (1) evaluate the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 86 publications
4
52
0
19
Order By: Relevance
“…In Europe, USA and Canada some studies tried to understand this (CLEVENGER et al, 2003;GRILO et al, 2009;GRILO et al, 2012;D'AMICO et al, 2015;GARRIGA et al, 2017) and concluded that temperature influences roadkill (D'AMICO et al, 2015;GARRIGA et al, 2017). In Brazil, we have just started, our researches investigate if there are more roadkill in the rainy or dry season (BUENO; ALMEIDA, 2010;RAMOS et al, 2011;BRAZ;FRANÇA, 2016) or the stretches of the highway with higher roadkill rates (CÁCERES et al, 2012;BUENO et al, 2012;SANTANA, 2012;FERREIRA et al, 2014;CARVALHO et al, 2015;ASCENSÃO et al, 2017;SANTOS et al, 2017). We still need to understand better the influence of climate variables on roadkill in tropical countries, such as Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, USA and Canada some studies tried to understand this (CLEVENGER et al, 2003;GRILO et al, 2009;GRILO et al, 2012;D'AMICO et al, 2015;GARRIGA et al, 2017) and concluded that temperature influences roadkill (D'AMICO et al, 2015;GARRIGA et al, 2017). In Brazil, we have just started, our researches investigate if there are more roadkill in the rainy or dry season (BUENO; ALMEIDA, 2010;RAMOS et al, 2011;BRAZ;FRANÇA, 2016) or the stretches of the highway with higher roadkill rates (CÁCERES et al, 2012;BUENO et al, 2012;SANTANA, 2012;FERREIRA et al, 2014;CARVALHO et al, 2015;ASCENSÃO et al, 2017;SANTOS et al, 2017). We still need to understand better the influence of climate variables on roadkill in tropical countries, such as Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the generalist behaviour of D. marsupialis and P. cancrivorus, the freeze antipredator response of C. thous, and the clumsy and slow terrestrial locomotion of T. mexicana have been invoked to explain the high road mortality rates of these species (Artavia et al 2015). Likewise, many species do not show car avoidance behaviour, increasing their roadkill probability, especially when population's densities are high (Jaeger et al 2005, Ascensão et al 2017. Moreover, wildlife communities with high species richness will be more susceptible to road mortality effects because a higher number of species are prone to be roadkilled (Ascensão et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, many species do not show car avoidance behaviour, increasing their roadkill probability, especially when population's densities are high (Jaeger et al 2005, Ascensão et al 2017. Moreover, wildlife communities with high species richness will be more susceptible to road mortality effects because a higher number of species are prone to be roadkilled (Ascensão et al 2017). Road size, road quality, and vehicular speed represent additional factors that could influence the number of local wildlife roadkills and deserve further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations